Evaluation of Sports Extracurricular Management During the Covid 19 Pandemic Middle School in the District of Tonjong Brebes (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
Extracurricular sports activities are activities conducted outside of school hours that are beneficial for increasing the physical fitness of students, because sports force children to move dynamically and exhibit appropriate physical behavior. This study's objectives are: 1) Evaluation of the management of extracurricular sports planning 2) Evaluation of the implementation management of extracurricular sports activities. 3) An evaluation of the supervision of extracurricular sports activities. 4) Evaluation of the evaluation of management of sports extracurricular activities at State Junior High Schools in the Tonjong District of the Brebes Regency. This is a qualitative study using a qualitative descriptive method. The sources of information for this study include the principal, the waka of student affairs, the eskul coaches, and the students. Observational, interview-based, and document-based data collection techniques. The four interacting components of data analysis are data collection, data reduction, data display, and conclusion. The results of planning research at Public Junior High Schools in Tonjong District, Brebes Regency indicated that, on average, a questionnaire is used to recruit sports extracurricular participants. This is evident from the recruitment stage of sports extracurricular participants, which is conducted simultaneously using a questionnaire form. Tonjong had a method of two training sessions, each of which lasts 45 minutes.. The research concludes that the extracurricular administration of SMPN in the Tonjong District has been successful. During the COVID-19 pandemic, the improvement of student performance in the field was impeded.